2016
DOI: 10.1007/s40670-016-0245-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel Modules to Teach Evolutionary Medicine: an Australian and a Swiss Experience

Abstract: Objectives Evolutionary medicine is a growing field focusing on the evolutionary basis of human diseases and their changes through time. The introduction of concepts of long-and shortterm evolution into the medical curricula is essential to acknowledge the variability of human biology. Methods Three courses of the EM taught at the University of Zurich and the University of Adelaide are presented by giving their general descriptions, full curricula, and the results of anonymized student evaluations. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As can be observed from the preceding discussion, evolution influences all aspects of human physiology and pathophysiology and can inform the developments of treatments that are rooted in mechanistic understandings of disease etiology (FIGURE 1). It is vitally important that medical curricula emphasize the evolutionary context of human physiology (29). In the future, we can anticipate improvements in molecular techniques that will better enable researchers in the field of evolutionary medicine to decipher ancient DNA and RNA, and such next-generation sequencing techniques will permit more thorough exploration of the genetic basis for ongoing evolution of physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…As can be observed from the preceding discussion, evolution influences all aspects of human physiology and pathophysiology and can inform the developments of treatments that are rooted in mechanistic understandings of disease etiology (FIGURE 1). It is vitally important that medical curricula emphasize the evolutionary context of human physiology (29). In the future, we can anticipate improvements in molecular techniques that will better enable researchers in the field of evolutionary medicine to decipher ancient DNA and RNA, and such next-generation sequencing techniques will permit more thorough exploration of the genetic basis for ongoing evolution of physiological processes.…”
Section: Discussionmentioning
confidence: 99%
“…Motivated to help increase the integration of human health into evolution education, Antolin et al [ 31 ] provided biomedical examples that exemplify evolutionary concepts that can be integrated into classrooms. Other articles have provided descriptive accounts of courses in evolution and medicine as guides to help others design their own courses [ 32 , 33 ] and several textbooks have recently been published on evolutionary medicine [ 34–36 ]. This prior work provides a platform that helps to initiate our attempt to create a consensus view of core principles for the field of evolutionary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Students in the program reported that they would recommend the course and gave high ratings to their perceived gains in understanding, averaging a 4.7 out of 5. Similar study modules in the UK, Switzerland and Australia were equally well-received and the students strongly appreciated the relevance to medicine [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%